A REVISIT OF VIETNAM-INDIA CULTURAL DIPLOMACY ACTIVITIES (2016–2021) AND ITS PROSPECTS - Ha, Trieu Huy (Trường Đại học Đà Lạt, 2024)
This article traces the evolution of Vietnam-India cultural relations between 2016 and 2021. The methodology of qualitative research design, data collection, and thematic and textual analysis are used to shed light on the rise of Vietnam’s and India’s cultural diplomacy. The article describes the substantial development in Vietnam-India cultural diplomacy between 2016 and 2021 with clear evidence of cultural events. Based on the closely examined process of India-Vietnam cultural relations and the national policies of Vietnam and India, the author provides an outlook for these bilateral cultural ties in the future.